Pendekatan Hermeneutika dalam Ilmu Tafsir - Ummi Inayati (STAIFAS-Press, 2019)
This article is a qualitative research research literature on hermeneutics in interpretation. This article was written to answer how hermeneutic approaches in the science of interpretation and hermeneutic perspective on the Qur'an. As a new methodology for the study of the holy book, the existence of hermeneutics is inevitable in the world of the Holy Qur'an. The mushrooming of a variety of contemporary interpretative literature that offers hermeneutics as a variable method of understanding the Koran shows how attractive the hermeneutic is indeed. Hassan Hanafi in his Religious Dialogue and Revolution states that Hermeneutics is not just a science of interpretation or theory of understanding, but also means a science that explains the acceptance of revelation from the word level to the world level. Knowledge of the process of revelation from letters to reality, from logos to praxis and also the transformation of revelation from the mind of God to human life